RELEVANSI RETORIKA DAN KOMUNIKASI DALAMAKTIVITAS DAKWAH - hemlan elhany; Wawan Trans Pujianto (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2022)
Rhetoric is a term that refers to art in communication with language as the main medium in its delivery with the aim of influencing the audience. Therefore rhetoric becomes significant in preaching so that messages can be conveyed effectively and efficiently so that it has an influence on society as an object of da'wah. This article aims to explain how rhetoric and communication in preaching are not only focused on linguistic aspects but also include other aspects by referring to the description of the verses of the Al-Qur'an and the practices carried out by the Prophet Muhammad SAW in preaching.